Effects of a Session of Exergames and Traditional Games on Inhibitory Control in Children With Autism Spectrum Disorder: Randomized Controlled Crossover Trial - Juliana Macedo Miranda; Rodrigo Alberto Vieira Browne; Weslley Quirino Alves da Silva; João Paulo Rodrigues dos Santos; Carmen Silvia Grubert Campbell; Isabela Almeida Ramos (JMIR Serious Games)
Abstract BackgroundAutism spectrum disorder (ASD) is characterized by deficits in executive functions, such as inhibitory control, which affect behavior and social adaptation. Although physical activity–based interventions, such as exergames, have shown potential to improve these functions, their comparative effects with active traditional games remain underexplored, particularly regarding inhibitory control in children with ASD. ObjectiveWe aim to analyze the effects of a session of exergames and active traditional games on inhibitory control in children with ASD. MethodsThis randomized controlled crossover trial included 9 male children with ASD (mean age 8.6, SD 1.4 y). Participants completed three 20-minute experimental sessions in random order, with a minimum interval of 48 hours: (1) active traditional games, (2) exergames using Just Dance 2022, and (3) a control session with manual painting activities. Inhibitory control was assessed 5 minutes postsession using a modified flanker task in the E-Prime (version 3.0; Psychological Software Tools Inc) program, recording reaction time (RT) and accuracy in congruent and incongruent phases. Repeated measures ANOVA was used to compare RT and accuracy between experimental and control conditions. Data are presented as means and 95% CIs. ResultsThere was a statistically significant effect of condition on RT in the incongruent phase (PPP ConclusionsA 20-minute session of exergame improved inhibitory control performance in children with ASD compared to active traditional games and painting activities.